Optical layer development for thin films thermal conductivity measurement by pulsed photothermal radiometry - Martan, J (The Review of scientific instruments, 2015)
Measurement of thermal conductivity and volumetric specific heat of optically transparent thin films presents a challenge for optical-based measurement methods like pulsed photothermal radiometry. We present two approaches: (i) addition of an opaque optical layer to the surface and (ii) approximate correction of the mathematical model to incorporate semitransparency of the film. Different single layer and multilayer additive optical layers were tested. The materials of the optical layers were chosen according to analysis and measurement of their optical properties: emissivity and absorption coefficient. Presented are thermal properties' measurement results for 6 different thin films with wide range of thermal conductivity in three configurations of surface: as deposited, added Ti layer, and added Ti/TiAlSiN layer. Measurements were done in dependence on temperature from room temperature to 500 °C. The obtained thermal effusivity evolution in time after the laser pulse shows different effects of the surface layers: apparent effusivity change and time delay. Suitability of different measurement configurations is discussed and results of high temperature testing of different optical layers are presented.